Effective Hamiltonian and excitation spectrum of harmonically trapped bosons: Бозе-эйнштейновская конденсация - Rovenchak, Andrij (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
An approach is proposed to obtain an effective Hamiltonian of a harmonically trapped Bose-system. Such a Hamiltonian is quadratic in the creation–annihilation operators and certain approximations allow to simplify higher (three and four operator) products to the required form. After the Hamiltonian diagonalization, the expression for the excitation spectrum is obtained containing in particular temperature-dependent corrections. Numerical calculations are made for a one-dimensional system. Some prospects towards the extension of the suggested approach to study binary bosonic mixtures are briefly discussed.